Perlindungan Hukum terhadap Harta Bawaan yang Bercampur dengan Harta Bersama Akibat Pengelolaan Bersama: Studi Kasus dan Analisis Yuridis - Parlaungan Gabriel Siahaan; Ramona Febiola Simorangkir; Adelia Br Aritonang; Grace Claudia Valerina Saragih; Joya Urmila Lubis; Peter Patiangbanua Purba; Trima Uasito Tampubolon (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to examine the legal protection of property brought into marriage that is mixed with joint property as a result of joint management in a marriage. In many cases, this mixing causes unclear legal status of the assets, especially during divorce or inheritance division. This study uses empirical normative legal methods with a qualitative descriptive approach. The data obtained were analyzed using data reduction, data presentation, and conclusion drawing techniques. This study shows that legal regulations in Indonesia related to the protection of property brought into marriage that is mixed with joint property due to joint management in marriage, and highlights the inconsistency of court decisions in such disputes and their impact on household economic stability. Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law have distinguished between property brought into marriage and joint property, practice in the field shows that mixing of property due to joint management often causes conflict during divorce. Inconsistency in court decisions arises due to the unclear norms in Article 37 of the Marriage Law which provide room for different interpretations by judges. This has an impact on legal uncertainty and potential injustice, especially for parties who are socially or economically weaker. Mixed property disputes also affect household economic stability, exacerbate social inequality, and cause psychological burdens for family members, including children. This study recommends the need for more detailed regulatory updates, the issuance of technical guidelines by the Supreme Court to unify decision standards, and increased legal education for the community to prevent conflicts through marriage agreements.